Implementasi Metode Algoritma KVC Untuk Pengamanan Pesan - Yunita Achsanty; Heru Abrianto; Ninuk Wiliani (STIKOM Tunas Bangsa Pematangsiantar, 2018)
Communication through message media or sms, Sort Message Service is not a point to point message but that communication by sent through sms network and stored in database operator. Message security on the network is threatened be read by people who are not responsible or called intercept. Therefore it will be develop some application on the mobile phone to modify the message be come a ciphertext and the information content of the messageis not known by others. In this application, the system encrypts the message into ciphertext using the key entered by the sender and then it will be sends to the destination number. For accepting the message, system will decrypt chipertext become plaintext using key by sender, then the message can be read by receiver. This application can be used by some one who wants to sending the secret message and very important without fear if the information can read by others. This application uses vigenere cipher method. The main parameter is the key and the message itself.